Efficacy and toxicity of intraperitoneal chemotherapy as compared to intravenous chemotherapy in the treatment of patients with advanced ovarian cancer. Issue 1 (7th August 2021) - Kim, Soyoun Rachel; Maganti, Manjula; Bernardini, Marcus Q.; Laframboise, Stephane; Ferguson, Sarah E.; May, Taymaa
Abstract: Objective: To assess the efficacy and toxicity of intraperitoneal (IP) chemotherapy compared to intravenous (IV) chemotherapy. Methods: Toxicity profiles, recurrence patterns, and long‐term survival outcomes of 271 women with Stage IIIC or IV high‐grade serous ovarian cancer (HGSC) treated with primary cytoreductive surgery followed by adjuvant IP or IV chemotherapy during 2001–2015 were reviewed. Results: Women who received IP chemotherapy ( n  = 91) were more likely to have undergone aggressive and longer surgery with no residual disease compared to the IV arm ( n  = 180). Chemotherapy‐related toxicities were comparable between the two groups. Extraperitoneal recurrences were more common in the IP arm compared to the IV arm. Five‐year progression‐free survival was 19% versus 18% ( P  = 0.63) and overall survival was 73% versus 44% ( P  < 0.01) in the IP versus IV arms, respectively. After adjustment for significant clinicopathologic factors in a multivariable model, use of IP was no longer a statistically significant predictor of overall survival. Conclusion: IP chemotherapy in advanced HGSC has not been widely adopted due to concerns about toxicity and inconvenience. Use of IP chemotherapy was associated with comparable safety profile and efficacy to IV chemotherapy in women with Stage IIIC/IV HGSC. Recurrences were more likely to be extraperitoneal with IP treatment. Synopsis: Intraperitoneal chemotherapy is well tolerated with comparable safety profile to intravenous chemotherapy. Extraperitoneal recurrences are more common with the use of IP chemotherapy.